The Effects of Gender and Parental Education on Participation Within Post-Secondary Education in the 1970s and 1980s - Guppy, Neil; Pendakur, Krishna (Canadian Journal of Higher Education, 1989)
Knowledge of factors affecting access to post-secondary education is growing, but we know much less about influences shaping patterns of study within higher education. This paper explores the impact of gender and parental education on student decisions to study part-time or full-time, to choose college or university, and to enroll in different fields of study. These issues are examined using representative national samples of Canadian students from 1974-75 and 1983-84. We demonstrate that both gender and family education play decisive roles in influencing patterns of participation in higher education and that the effects of family background differ significantly between women and men.